NEW KIND OF IIR DIGITAL FILTERS INTENDED FOR PULSE PERIOD FILTERING (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This paper describes a new kind of infinite impulse response (IIR) digital filter designed for pulse period filtering. The IIR digital filter is designed using a third-order IIR frequency locked loop (IIR FLL), which is based on the time measurement and processing of both, the input and output periods. A general form of the difference equation describing this type of IIR FLL of any order is developed and compared with the corresponding difference equation of classical digital filters. The mathematical analyses in the time domain were performed using the Z transform approach and the theory of linear discrete systems. An analysis of the IIR digital filter was performed in the time and frequency domain. The transfer functions and Z transform of the third-order IIR FLL outputs are developed. The main part of the article is devoted to designing the appropriate IIR FLL digital filter using the corresponding IIR FLL. For this purpose, the theory of IIR digital filter and the corresponding MATLAB tools are used, but taking into account the differences between these systems. The filtering abilities of the designed IIR FLL digital filter are demonstrated. Computer simulation of the designed IIR FLL is made in the time domain to enable precise insight into its properties.
Keywords: Frequency Locked Loop; Digital filter; Phase Locked Loop; Digital circuit; Discrete Linear System